Insight into the molecular mechanisms of leaf coloration in Cymbidium ensifolium - Cao, Hua; Li, Han; Chen, Xiang; Zhang, Yuying; Lu, Lin; Li, Shenchong; Tao, Xiang; Zhu, WeiYin; Wang, Jihua; Ma, Lulin (Frontiers in Genetics, 2022)
Cymbidiumensifolium L. is a significant ornamental plant in Orchidaceae. Aside from its attractive flowers, its leaf coloration is also an important ornamental trait. However, there is an apparent lack of studies concerning the intricate mechanism of leaf coloration in C. ensifolium. In this study, we report a systematic evaluation of leaf coloration utilizing transcriptome and metabolome profiles of purple, yellow, and green leaves. In total, 40 anthocyanins and 67 flavonoids were quantified along with chlorophyll content. The tissue–transcriptome profile identified 26,499 differentially expressed genes (DEGs). The highest chlorophyll contents were identified in green leaves, followed by yellow and purple leaves. We identified key anthocyanins and flavonoids associated with leaf coloration, including cyanidin-3-O-sophoroside, naringenin-7-O-glucoside, delphinidin, cyanidin, petunidin, and quercetin, diosmetin, sinensetin, and naringenin chalcone. Moreover, genes encoding UDP-glucoronosyl, UDP-glucosyl transferase, chalcone synthesis, flavodoxin, cytochrome P450, and AMP-binding enzyme were identified as key structural genes affecting leaf coloration in C. ensifolium. In summary, copigmentation resulting from several key metabolites modulated by structural genes was identified as governing leaf coloration in C. ensifolium. Further functional verification of the identified DEGs and co-accumulation of metabolites can provide a tool to modify leaf color and improve the aesthetic value of C. ensifolium.